Avalanches of electrons in a gas. (24th August 2016) - Steutel, F. W.
Abstract : The motion of electrons through a gas of particles is modelled as a two-state process: an electron is alternatingly moving and being held captive by a non-moving particle, during exponentially distributed periods. The model contains a parameter p, the probability that collision of an electron with a gas particle does not lead to its capture but produces an extra electron. The quantity of interest is the current C ( t ) produced by the moving electrons, as a function of time.